2020
DOI: 10.1001/jamaneurol.2019.4271
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Cigarette Smoking and Multiple Sclerosis

Abstract: ultiple sclerosis (MS) is a chronic neurologic disorder characterized by demyelination and axonal loss in the central nervous system (CNS). 1 Environmental factors play a central role in the cause of MS. The most important environmental risk factors include cigarette smoking, Epstein-Barr virus infections, vitamin D deficiency, and obesity. 2,3 Cigarette smoking is a widespread habit with 2 billion consumers worldwide-a total of 5.8 trillion cigarettes are consumed each year. Smoking is associated with an incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
70
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 109 publications
4
70
1
Order By: Relevance
“…Several studies have observed increased Expanded Disability Status Scale (EDSS) scores and Multiple Sclerosis Severity Score (MSSS) among smokers compared to nonsmokers [1]. Smoking has been associated with the rate of conversion from relapsing remitting to secondary progressive disease, and with time from MS onset to fixed disability milestones as measured by EDSS [1]. The association is supported by the presence of a dose-response effect of smoking on disability in terms of EDSS and MSSS changes [2].…”
Section: Clinical Studiesmentioning
confidence: 98%
See 3 more Smart Citations
“…Several studies have observed increased Expanded Disability Status Scale (EDSS) scores and Multiple Sclerosis Severity Score (MSSS) among smokers compared to nonsmokers [1]. Smoking has been associated with the rate of conversion from relapsing remitting to secondary progressive disease, and with time from MS onset to fixed disability milestones as measured by EDSS [1]. The association is supported by the presence of a dose-response effect of smoking on disability in terms of EDSS and MSSS changes [2].…”
Section: Clinical Studiesmentioning
confidence: 98%
“…However, a variety of methods and outcome measures have been used, making it difficult to draw conclusions across studies. Several studies have observed increased Expanded Disability Status Scale (EDSS) scores and Multiple Sclerosis Severity Score (MSSS) among smokers compared to nonsmokers [1]. Smoking has been associated with the rate of conversion from relapsing remitting to secondary progressive disease, and with time from MS onset to fixed disability milestones as measured by EDSS [1].…”
Section: Clinical Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Tobacco smoke has received increasing attention as a potential environmental risk factor for MS (Öberg et al, 2011; Carreras et al, 2019). Adult population case-control studies have shown that smoking or exposure to environmental tobacco smoke (ETS) promotes the disease progression and increases the recurrence of MS (Alphonsus and D’Arcy, 2019; Rosso and Chitnis, 2020). However, evidence for the impact of early-life exposure to ETS on adulthood MS development is not certain and even conflicting in the literature (Montgomery et al, 2008; Pantazou et al, 2015; Pronovost and Hsiao, 2019).…”
Section: Introductionmentioning
confidence: 99%